Changes in flavour, emotion, and electrophysiological measurements when consuming chocolate ice cream in different eating environments. (October 2019) - Xu, Yun; Hamid, Nazimah; Shepherd, Daniel; Kantono, Kevin; Spence, Charles
Highlights: Sensory attributes of ice cream rated differently in different environments. Positive and negative emotions were related to environment pleasantness. Sweet and bitter ratings were related to positive and negative emotions, respectively. SC and HR measures were significantly different in the different eating environments. Abstract: The eating context influences eating behaviour as well as the hedonic response to food. This study investigated temporal changes in the perceived flavour of chocolate ice cream when consumed in a laboratory, café, university study area, and a city bus stop, and further examined how emotion and electrophysiological measures were influenced by these environments. In this study, three measures were obtained from 160 participants. First, temporal changes in multisensory flavour perception after consuming chocolate ice cream in different environments were determined using the Temporal Dominance of Sensations (TDS) method. Second, participants' emotional responses were measured after consuming ice cream using a check-all-that-apply (CATA) list of emotions. Finally, standard electrophysiological measures of heart rate (HR), blood volume pulse (BVP), and skin conductance (SC) were also obtained. When ice cream was consumed in the café, it was associated with positive emotions and a sweet taste/flavour. When consumed in the university study area, it was correlated with both positive and negative emotions, and cocoa and milky flavours. Consumption at the city bus stop was correlated with the most negative emotions, and with roasted and bitter tastes/flavours. The laboratory environment was only correlated with the attributes of 'concentrating' and creamy flavour. SC was significantly increased in the university study area as compared to the laboratory, and HR was significantly decreased in the university study area environment as compared to the bus stop. The evidence from this study therefore indicates that the eating context constitutes an important factor to consider when carrying out sensory testing as participants' emotions, perceptions, and electrophysiological responses are influenced differently dependent upon the eating context.